Identifikasi Variabel Makro Ekonomi Di Provinsi Jawa Tengah - Wahyu R., Tri (Jurnal Ekonomi Kuantitatif Terapan, 2015)
The economic growth of Central Java have been facing some good phases over the period of stabilization and rehabilitation (1967-1972), the golden age of oil (1973-1982), the period of external shocks I (1983-1986), the era of the rise of non-oil exports (1987-1996), the period of external shocks II (1997-1998), and the period of economic stabilization after crisis (1999-2003). Therefore, this study aimed to analyze the economic growth of Central Java Province based on the identified macroeconomic variables, especially in terms of spending and to see the amount of labor absorbed in every field of business. The data used for modeling the application is secondary data and annual time series from 1995 until 2011. The result of this study showed that macroeconomic variable in terms of spending (real sector) which directly affects regional gross domestic regional product of Central Java, consists of: household consumption (C), government consumption (G), private consumption (I), exports (X). Meanwhile, imports does not directly affect gross domestic regional product of Central Java. There are also six (6) business sectors in Central Java Province which are able to increase the absorption of labor every increase of its output that is showed by the number of positive working elasticity. These business sectors are: manufacturing; electricity, gas, and water supply; construction; trade, hotels and restaurants; finance, leasing & services companies, and services. But, there are three business sectors whose working elasticity is negative, it means that although the ouput generated increases, but its absorption towards labor is low (decrease). These three business sectors are: agriculture; mining & quarrying; and transportation & communication.
Keywords: economic growth; business sector; working elasticity; macroeconomic variable; gross domestic regional product